CT fluoroscopy‐guided pancreas transplant biopsies: a retrospective evaluation of predictors of complications and success rates. (13th March 2021) - Fehrenbach, Uli; Thiel, Regina; Bady, Patricia‐Desiree; Auer, Timo A.; Kahl, Andreas; Geisel, Dominik; Lopez Hänninen, Enrique; Öllinger, Robert; Pratschke, Johann; Gebauer, Bernhard; Denecke, Timm
Summary: To identify predictors of biopsy success and complications in CT‐guided pancreas transplant (PTX) core biopsy. We retrospectively identified all CT fluoroscopy‐guided PTX biopsies performed at our institution (2000–2017) and included 187 biopsies in 99 patients. Potential predictors related to patient characteristics (age, gender, body mass index (BMI), PTX age, PTX volume) and procedure characteristics (biopsy depth, needle size, access path, number of samples, interventionalist's experience) were correlated with biopsy success (sufficient tissue for histologic diagnosis) and the occurrence of complications. Biopsy success (72.2%) was more likely to be obtained in men [+25.3% (10.9, 39.7)] and when the intervention was performed by an experienced interventionalist [+27.2% (8.1, 46.2)]. Complications (5.9%) occurred more frequently in patients with higher PTX age [OR: 1.014 (1.002, 1.026)] and when many (3–4) tissue samples were obtained [+8.7% (−2.3, 19.7)]. Multivariable regression analysis confirmed male gender [OR: 3.741 (1.736, 8.059)] and high experience [OR: 2.923 (1.255, 6.808)] (biopsy success) as well as older PTX age [OR: 1.019 (1.002, 1.035)] and obtaining many samples [OR: 4.880 (1.240, 19.203)] (complications) as independent predictors. Our results suggest that CT‐guided PTX biopsy should be performed by an experienced interventionalist to achieve higher success rates, and not more than two tissue samples should be obtained to reduce complications. Caution is in order in patients with older transplants because of higher complication rates.